Uncovering the hidden face of narrative analysis: A reflexive perspective through MAXQDA. (November 2021) - Consoli, Sal
Abstract: Despite some struggles in acquiring full recognition, narrative inquiry is now well-established in applied linguistics, especially within the domain of language learning and teaching. Most importantly, there is a growing body of literature which specifically addresses methodological issues related to applied linguistics (e.g., Barkhuizen, 2013; Bell, 2002, 2011; Benson, 2018). This article extends the epistemological debates which have characterised narrative inquiry over the past decade and puts the spotlight on a specific method, narrative analysis, the process of writing stories as an approach to data analysis and representation of research findings. In particular, I will unpack my experience of doing narrative analysis through MAXQDA, a Computer Assisted Qualitative Data Analysis (CAQDAS) Software. The use of this software did not only facilitate narrative analysis whilst dealing with a large dataset and different data sources, but also supported my engagement with researcher reflexivity, thereby legitimizing further the rigour of this narrative methodology.